2021
DOI: 10.1371/journal.pone.0248524
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of trimethoprim-sulfamethoxazole for the prevention of pneumocystis pneumonia in human immunodeficiency virus-negative immunodeficient patients: A systematic review and meta-analysis

Abstract: Background Pneumocystis pneumonia (PCP) has a significant impact on the mortality of immunocompromised patients. It is not known whether the prophylactic application of trimethoprim-sulfamethoxazole (TMP-SMZ) can reduce the incidence of PCP and mortality in the human immunodeficiency virus (HIV)-negative immunodeficient population. The safety profile is also unknown. There have been few reports on this topic. The aim of this study was to systematically evaluate the efficacy and safety of the use of TMP-SMZ for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…1 The results of recent meta-analyses have shown that TMP-SMX is useful for preventing and treating Pneumocystis jirovecii pneumonia (PCP) in immunocompromised patients. 2,3 However, the daily dosage of TMP-SMX varies greatly depending on whether the drug is used for treatment or prophylaxis. Some patients take TMP-SMX orally at 80-400 mg/day, whereas others take 960-4800 mg/ day.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…1 The results of recent meta-analyses have shown that TMP-SMX is useful for preventing and treating Pneumocystis jirovecii pneumonia (PCP) in immunocompromised patients. 2,3 However, the daily dosage of TMP-SMX varies greatly depending on whether the drug is used for treatment or prophylaxis. Some patients take TMP-SMX orally at 80-400 mg/day, whereas others take 960-4800 mg/ day.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…The incidence of PCP was more than 50% in immunocompromised patients, 22–45% in patients with hematological malignancy, 5–15% in transplant recipients and around 2% in patients with rheumatoid diseases [ 3 , 4 ]. The clinical indications of PCP, such as tachycardia, hypoxia, tachypnea, shortness of breath, etc., are the major causes of death of immunosuppressive patients [ 5 ]. Therefore, PCP is considered a hallmark disorder indicating human immunodeficiency virus (HIV) infection [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical indications of PCP, such as tachycardia, hypoxia, tachypnea, shortness of breath, etc., are the major causes of death of immunosuppressive patients [ 5 ]. Therefore, PCP is considered a hallmark disorder indicating human immunodeficiency virus (HIV) infection [ 5 ]. In the past few years, the occurrence or recurrence of PCP in HIV-positive patients has been reduced due to advanced technology and tools in diagnostic process, allowing early diagnosis; advanced management strategies in intensive care setting; and advanced preventive measures [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged treatment with high-dose steroids is a major risk factor for pneumocystis pneumonia (PCP) in patients with rheumatic diseases. 1 Patients with immune dysfunction induced by an inflammatory disease who receive more than 20 mg/d prednisolone for longer than 2 to 3 weeks should receive PCP prophylaxis. 2 - 5 Prophylactic trimethoprim-sulfamethoxazole (TMP/SMX) substantially decreases the incidence of PCP in patients with rheumatic diseases who receive prolonged, high-dose steroid treatment.…”
Section: Introductionmentioning
confidence: 99%